(untitled) (Palimpsesto, 2025)
This review addresses Julia Risso Villani’s work, inviting readers to read "Curvatures" as a dissonant challenge to the canons through which disability as an experience is conceived, imagined, and represented. The text offers a possible path to literary immersion in the embodied life, with humor, pain, and empathy.